RESPONSIBILITY AS THE FOUNDATION OF ETHICS: POLITICAL, TECHNOLOGICAL AND ECONOMIC RESPONSIBILITY - Dahl Rendtorff, Jacob (Revista do Programa de Pós-Graduação em Direito, 2016)
In this paper I would like to show the importance of the concept of responsibility as the foundation of ethics in particular in the fields of politics and economics in the modern civilisation marked by globalization and technological progres. I consider the concept of responsibility as the key notion in order to understand the ethical duty in a modern technological civilisation. We can indeed observe a moralization of the concept of responsibility going beyond a strict legal definition in terms of imputability. The paper begins by discussing the humanistic foundations of such a concept of responsibility. It treats the historical origins of responsibility and it relates this concept to the concept of accountability. On the basis of this historical determination of the concept I would like to present the definition of the concept of responsibility as fundamental ethical principle that has increasing importance as the foundation of the principles of governance in modern welfare states. In this context the paper discusses the extension of the concept of responsibility towards institutional or corporate responsibility where responsibility does not only concerns the responsibility of individuals but also deals with the responsibility of institutional collectivities. In this way the paper is based on the following structure : 1) The ethical foundation of the concept of responsibility 2) Responsibility in technological civilisation 3) Political responsibility for good governance in the welfare state 4) Social responsibility of business corporations in times of globalization 5) Conclusion and discussion : changed conditions of responsibility in modern times.